Impact of Corporate Governance on the Disclosure of Elements of Social Responsibility: Case on Saudi Industrial Companies - Alnaim, Musaab (The Arab Journal of Administration, 2025)
Corporate governance is considered a fundamental element to organize a company’s relationship with stakeholders, as it aims to balance between the objectives of individuals, societal, economic and social. Therefore, this study aims to measure the impact of corporate governance on the disclosure of corporate social responsibility elements of the joint-stock companies listed on the Saudi Stock Exchange (Tadawul). The study adopts several methodologies. The historical approach was used by reviewing previous studies to formulate the research problem. The deductive approach was employed to develop the study’s hypotheses. Finally, the descriptive analytical approach was used to analyze the data.The study sample included industrial joint-stock company represented by the Basic Materials sector for the year 2019 AD. Social disclosure and statistical tests to measure the impact of the characteristics of boards of directors, including each of: (Board size, Board independence, government ownership, members ’remuneration) on the level of disclosure of the elements of social responsibility.The study found that the increase in independent members in boards of directors limits the level of disclosure of the elements of social responsibility, and that the remuneration of members is not considered one of the determinants of disclosure in the companies of the study sample, while the results did not show a moral relationship between the size of the board and government ownership and the level of disclosure elements of social responsibility.